2008
DOI: 10.1007/s00417-008-0894-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary vitrectomy with Densiron-68 for rhegmatogenous retinal detachment

Abstract: With Densiron-68, high anatomical and functional success rates can be achieved with primary vitrectomy for RRD and predominantly inferior pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 27 publications
(31 reference statements)
2
41
0
5
Order By: Relevance
“…Other Oxane HD articles have found emulsification in up to 10.5%; with pseudohypopyon being described in one other case series [8]. As for Densiron 68, emulsification was present in up to 23% and was deemed to have low clinical impact in some studies [11,13,14,15,16,17]. However, in the initial series of Sandner and Engelmann [12], emulsification was severe enough in 8% (4 of 48 eyes) to result in pseudohypopyon formation [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other Oxane HD articles have found emulsification in up to 10.5%; with pseudohypopyon being described in one other case series [8]. As for Densiron 68, emulsification was present in up to 23% and was deemed to have low clinical impact in some studies [11,13,14,15,16,17]. However, in the initial series of Sandner and Engelmann [12], emulsification was severe enough in 8% (4 of 48 eyes) to result in pseudohypopyon formation [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, in eyes with scleral buckling, endotamponade with Oxane HD was found to have low retinal reattachment success rates (26%); the authors suggest that this may be due to poor affinity to the retinal surface, or insufficient specific density to provide adequate tamponade to areas adjacent to the indent [7]. The retinal reattachment rate with Densiron 68 endotamponade was 33–91% after the initial procedure, and 75–94% with further surgery [11,12,13,14,15,16,17]. It had been observed that Densiron 68 enabled better anatomic reattachment for complicated RD when compared to conventional 5,000-cs silicone oil, but adverse effects were similar [14].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these comparisons, we found the rate of success to be satisfactory given the cohort of patients treated. Inferior retinal detachments have been treated in previous reports with heavy silicone oils (mixtures of various heavy liquids and silicone oil with specific gravity >1.00) with good anatomical results [27][28][29][30][31] . As with pure silicone oil, complications include raised IOP, emulsification, and inflammatory responses [32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years it has gained increasing popularity, thanks to more and more encouraging anatomical and functional results. 1,2 The drawback of the use of Densiron-68 may be related to the difficulty of its removal. The gravity acting on the bubble, the force of adhesion between Densiron-68 and the retina, and its viscosity may cause special problems during its removal.…”
Section: Introductionmentioning
confidence: 99%